Chronic pelvic pain in women: comparative study between ultrasonography and laparoscopy as diagnostic tool - Rawat, Rajani; Seth, Shikha; Rawat, Ramakant; Garg, Ruchika; Shukla, Sushil; Vishwakarma, Soniya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Chronic pelvic pain is a major cause of morbidity among the reproductive age group women. The study on patients of chronic pelvic pain aimed to compare the diagnostic accuracy of ultrasonography and laparoscopy in these patients Methods: The study was conducted on 100 patients of chronic pelvic pain attending the gynaecology outdoor and were subjected to thorough clinical examination followed by ultrasonography and laparoscopic examination. Results: Maximum number of cases of chronic pelvic pain belonged to 25-30 years, were parous with mean duration of pain of 15.2 months. The most common complaint was vaginal discharge (70%) followed by menstrual irregularity. On clinical examination, pelvic tenderness was observed in majority (60%) of cases. USG examination showed chronic pelvic inflammatory disease in 43% cases followed by myoma (8%), ovarian cyst (5%), endometriosis (6%), pelvic congestion (5%) and no abnormal pathology in 25% cases. On laparoscopic examination, chronic pelvic inflammatory disease was present in 47% cases followed by endometriosis (11%), pelvic congestion (8%), myoma (8%), adhesions (7%) while 13% cases showed normal findings. Conclusions: Laparoscopy is more effective than ultrasonography as a diagnostic tool in patients of chronic pelvic pain.